2021
DOI: 10.1038/s41467-020-20548-8
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and elucidation of the lipoinitiation process in nonribosomal peptide biosynthesis

Abstract: Nonribosomal peptide synthetases containing starter condensation domains direct the biosynthesis of nonribosomal lipopeptides, which generally exhibit wide bioactivities. The acyl chain has strong impacts on bioactivity and toxicity, but the lack of an in-depth understanding of starter condensation domain-mediated lipoinitiation limits the bioengineering of NRPSs to obtain novel derivatives with desired acyl chains. Here, we show that the acyl chains of the lipopeptides rhizomide, holrhizin, and glidobactin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 71 publications
(141 reference statements)
1
59
0
Order By: Relevance
“…The hty BGC provides an important biosynthetic precursor L-homotyrosine which was recognized by the fourth A domain of the NRPS EcdA. Understanding the biosynthetic mechanism of echinocandin B will facilitate us to take advantage of synthetic biology techniques to bioengineer NRPSs to generate bioactive compounds [ 49 , 50 , 51 ].…”
Section: Fungal Non-ribosomal Peptide Biosynthesis Involving Two Sepa...mentioning
confidence: 99%
“…The hty BGC provides an important biosynthetic precursor L-homotyrosine which was recognized by the fourth A domain of the NRPS EcdA. Understanding the biosynthetic mechanism of echinocandin B will facilitate us to take advantage of synthetic biology techniques to bioengineer NRPSs to generate bioactive compounds [ 49 , 50 , 51 ].…”
Section: Fungal Non-ribosomal Peptide Biosynthesis Involving Two Sepa...mentioning
confidence: 99%
“…A fully saturated fatty acid residue can be found in puwainaphycins, minutissamides, muscotoxins, and laxaphycins Gregson et al, 1992;Neuhof et al, 2005), while a set of polyunsaturated fatty acid is found in anabaenolysins (Jokela et al, 2012). Bacterial cyclic lipopeptides are synthesized through complex secondary metabolic pathways (Chooi & Tang, 2010;Roongsawang et al, 2010;Zhong et al, 2021). Fatty acyl chains are the first monomers incorporated into the peptidyl backbone via a process known as lipoinitiation (Chooi & Tang, 2010;Zhong et al, 2021).…”
Section: Chemical Structure and Biosynthesis Of Cyanobacterial Lipopeptidesmentioning
confidence: 99%
“…Bacterial cyclic lipopeptides are synthesized through complex secondary metabolic pathways (Chooi & Tang, 2010; Roongsawang et al, 2010; Zhong et al, 2021). Fatty acyl chains are the first monomers incorporated into the peptidyl backbone via a process known as lipoinitiation (Chooi & Tang, 2010; Zhong et al, 2021). The lipid residue can be incorporated in a number of ways (Figure 2, Chooi & Tang, 2010).…”
Section: Chemical Structure and Biosynthesis Of Cyanobacterial Lipopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccharochelins harbor linear or branched fatty acyl chains ranging from C12 to C15, but foroxymithine contains only an acetyl chain (C2), which implied that SacE_C S might possess flexible but comparatively higher specificity toward longer fatty acid groups, resulting in the diverse amphiphilic saccharochelin derivatives (Figure S4). Based on our recent progress in genetic engineering and structural exploration of RzmA_C S , the C S domain of the rhizomide biosynthetic synthetase RzmA, 26 we also investigated the key residues in defining the length of fatty acyl chains in SacE_C S by alignment and structure homology modeling (Figure S5). The W29, Y123, and C133 residues in SacE_C S corresponding to Q36, Y138, and R148, respectively, in RzmA_C S were predicted to control the length of acyl donors (Figure S5).…”
mentioning
confidence: 99%